PENGEMBANGAN MEDIA SOSIALISASI ”DISIPLIN LALU LINTAS” UNIT DIKYASA DENGAN ANIMASI MOTION GRAPHIC DAN KONSEP ART ANIMASI ”STUDI KASUS: UNIT DIKYASA SATLANTAS POLRES BULELENG” - Made Windu Cahyadi; I Ketut Resika Arthana; I Made Ardwi Pradnyana (Universitas Pendidikan Ganesha, 2020)
The purpose of this research is to develop an animated film for socialization of Unit Dikyasa Satlantas Polres Buleleng in discipline behave in traffic. This animated film has the exact same storyline with the real situation.Development of animated films dissemination of this traffic using Multimedia Development Life Cycle (MDLC) models. Which consists of six stages: Concepts, Design, Material Collecting, Assembly, Testing, and Distribution. The Concept consisting of animation specification analysis. The Design consisting of Character Design based on Concept Art, Audio Recording, Choosing Music/Sound Effects and Background Design. The Material Collecting consisting of collecting the material like teks, images, and audio. The Assembly consisting of 2 stages, Production and Post-Production. On Production consisting of illustration, animation and first rendering process. On Post-Production consisting of audio recording and editing, video editing, and last rendering process. The Testing consisting of content, media, user respond testing. The Distribution consisting of distribute by online and offline method. Implementation of traffic discipline animation is done through expert testing content and media expert test to determine the validity of the contents of the animation from the animation that has been made. While testing the user response is done by giving questionnaires to students and the general public. The average response of the students and the community, animation of traffic discipline that is 87.73%, and if the response is converted into a table, it categorized as a “Good” animation category.Keywords : Film Animation, Socialisation, Lalu Lintas, Concept Art, MDLC